Using Action Strategy in Improving Speaking Skill in English Language Teaching - Sitti Nurjannah; Endang Ruswiyani (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2022)
This research aims to improve the speaking skill through the use of of Action Learning Strategy of the Eight Grade Students in English Language Teaching. This research was conducted in SMPN 3 Soromandi Kabupaten Bima, NTB. This research is designed quantitatively by using time series design. The sample was taken through cluster random sampling. There were 40 students were taken as a sample. In collecting the data, the instrument used was speaking test to know the improvement of student ability in speaking skill. The test were pre-test and post-test. The result of data analysis shows that an improvement of students’ scores in pretest 1 to 4. The mean score of pretests 1 is 59.13, in pretest 2 was 62.0, in pretest 3 was 56.5, and pretest 4 was 58.38. On the contrary, the result of posttest shows the improvement of the students score in posttest 1 is 70.38, posttest 2 is 72.75, posttest 3 is 76.75, and posttest 4 is 74.90. Based on the result of pretest and posttest shows that the use of Action Learning Strategy can improve the speaking skill in English Language Teaching. In conclusion, the use of Action Learning Strategy is effective in improving the speaking skill in English Language Teaching.